Conceptual principles of ecologically safe development of aquaculture - Olga Iermakova; Iryna Zhuvahina; Volodymyr Metelytsia; Roman Dmytryshyn (4th International Conference on Environmental Sustainability in Natural Resources Management 2024 (ISCES 2024) 31/10/2024 - 31/10/2024 Online, 2024)
In the past, when the aquaculture industry was just beginning to develop in the world, the main goal of fish farming was to provide the population with food. The development of fish farming led to the emergence of environmental problems, which made it necessary to include the factor of environmental safety, along with economic and social factors, into the agenda of the development of the aquaculture sector. The purpose of this study is to determine the conceptual basis for the implementation of environmental safety principles for the development of the aquaculture sector. The article examines the peculiarities of aquaculture development in terms of modern ecological concepts, the mutual influence of factors of ecologically safe market-oriented development of aquaculture, the sustainable development model of the aquaculture sector is proposed, the tools for ensuring ecologically safe market-oriented development of the aquaculture sector are systematized.
Conference: 4th International Conference on Environmental Sustainability in Natural Resources Management 2024 (ISCES 2024)
Keywords: 330